Humanismo educativo en las sociedades del conocimiento: oportunidades para la juventud de Guanacaste, Costa Rica - Castellón Zelaya, Luis Arturo (2018)
This document presents an analysis of limitations and factors that make possible the existence of gaps in Costa Rican public education, in specific, in the context of the province of Guanacaste. The information is based on the results of a research on the quality of teaching for the use of ICT, reading and writing in the native language and second languages in primary and secondary schools in the city of Liberia, in Guanacaste. The results show that there are still inequities in the quality of public education that limits the development of technical and academic skills of young people in rural areas and, therefore, their possibilities of accessing job opportunities in a globalized society.